Group organization, elections and urban political mobilization in the developing world. Issue 8 (17th November 2021) - Thomson, Henry; Buhaug, Halvard; Urdal, Henrik; Rosvold, Elisabeth
ABSTRACT: Elections generate incentives for contention and violence. However, collective action problems mute responses to strategic incentives by unorganized individuals, relative to organized groups. Variation in the severity of collective action problems and the degree of strategic behaviour results in distinct patterns of mobilization across these two types of groups that have been overlooked in previous literature. We explore variation in organized and unorganized political mobilization and violence at elections using new event data for over one hundred cities in the developing world from 1960 to 2014. We find that organized groups are more likely to mobilize before elections to influence their outcome, and under permissive opportunity structures at moderate levels of democracy. Mobilization by unorganized individuals occurs at and directly after elections but does not vary by regime type. Distinct mobilization patterns across group type are a major addition to our understanding of the link between elections, democracy, contention and violence.